(untitled) (Bangladesh Journal of Endosurgery, 2014)
Purpose: To evaluate the outcome of prenatally diagnosed posterior urethral valve (PUV) patients in our setup where fetal interventions are not available. Methods: This prospective study included 24 PUV patients (July 2007 to December 2012), who were diagnosed prenatally but had no prenatal interventions and delivered in our center. Within 24 hours after birth, all of them had urinary ultrasonography (USG). Voiding cystourethrography (VCUG) and renogram were done in the second week and cystoscopy with valve ablation during the same admission period. Patients were followed up regularly after cystoscopic fulguration. Clinical features, treatment, and outcomes were analyzed. Results: Predominant clinical features were renal failure and urinary ascites. Eleven patients (45.8%) had bilateral vesicoureteric reflux (VUR) of different grades. Eight patients (33.3%) had decreased renal cortical thickness (<10 mm). All patients underwent cystoscopic fulguration except three (expired before fulguration). Four patients (16.6%) needed cutaneous vesicostomy along with fulguration. Follow up period ranged from 3 months to 6 years. At last follow-up, 9 (37.5%) boys had renal failure; 7 patients (29%) had normal renal parameters with good urinary stream. Mortality was 7 (29%) including 3 who died before fulguration. Conclusion: Prenatally detected PUV children seem to have both morphologically and functionally compromised urinary system with poor outcome. DOI: http://dx.doi.org/10.11593/bje.2013.0103.0022 Bangladesh Journal of Endosurgery Vol.1(3) September 2013: 20-23